Enhanced Performance via π‐Bridge Alteration of Porphyrin‐Based Donors for All‐Small‐Molecule Organic Solar Cells. Issue 6 (27th January 2023) - Shen, Haojiang; Ren, Yi; Li, Jianfeng; Xu, Yixuan; Han, Chenyang; Zou, Wentao; Xu, Huajun; Sun, Yanna; Kan, Yuanyuan; Gao, Ke
Comprehensive Summary: All‐small‐molecule organic solar cells (ASM OSCs) are promising for commercial application due to the well‐defined chemical structures, convenient purifying process and low batch‐to‐batch variation. However, the similarity of molecule structures between small molecule donors and acceptors makes a hard regulation of their blend morphology, which will limit the efficiency. One of the efficient approaches is structural tuning, among which the π‐bridge engineering is considered as a good method to improve the blend morphology. Herein, we synthesized two porphyrin‐based small‐molecule donors, Por‐BR and Por‐TR, by introducing alkoxybenzene and alkylthiophene as π bridges. The Por‐BR‐based active layer produces poor morphology and does not achieve satisfying device efficiency because of the excessive aggregation tendency. As for Por‐TR, an efficiency of 11.26% is achieved with such a high open circuit voltage of 0.904 V. This study shows that altering π‐bridge units can facilitate the improvement of film morphology, finally increase the device performance, and also provides a sample for molecule designing in terms of structure‐property correlation. Abstract : Two porphyrin‐based small‐molecule donors, Por‐BR and Por‐TR, were synthesized by introducing alkoxybenzene and alkylthiophene as π bridges for all‐small‐molecule organic solar cell devices. The Por‐BR‐based active layer produces poor morphology and does not achieve satisfying device efficiency because of the excessive aggregation tendency. And as for Por‐TR, an efficiency of 11.26% is achieved with such a high open circuit voltage of 0.904 V. This study shows that altering π‐bridge units can facilitate the improvement of film morphology, finally increase the device performance, and also provides a sample for molecule designing in terms of structure‐property correlation.